To Calculation of Electro-Dynamic Resonant System of Resonance Generators - V. K. Moroz; A. A. Polischuk; G. A. Mikhaltsevich; E. M. Satsukevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
The paper provides an original calculative and graphical method for determination of resonant generator system parameters.